ASSESSMENT OF POTENTIAL LOCATIONS FOR BONUS ZONING IN BANDUNG - S. D. Hasan, Tika; Zulkaidi, Denny (PLANNING MALAYSIA, 2018)
Despite being a common practice in other countries, bonus zoning is still relatively new in Indonesia. Bonus zoning is a zoning regulation tool that allows developers to increase density in exchange for the improvement or provision of public facilities. Bandung, in particular, has already designated areas for bonus zoning within its Local By-law No.10/2015 concerning Detailed Spatial Plan and Zoning Regulation. Its detailed mechanism however is not yet implemented. This research seeks to investigate a) the rationale behind the application of bonus zoning in Bandung; b) the carrying capacity of the areas where bonus zoning could be applied; c) the type of public space to be provided as development compensation; and d) the calculation for compensation. Content analysis was used to review literature and legal documents regarding planning and development in Bandung. This research expects to find which areas are suitable for implementing bonus zoning and come up with its compensation as the basis for sustainable planning in Bandung that not only benefits the developers but also the public as a whole.